Evaluation of follow-up observation using human epididymis protein 4, a tumor marker, in patients with ovarian cancer - Masaya Uno; Rie Matsuo; Naoki Maezawa; Tomoyasu Kato (Korean Society of Obstetrics and Gynecology, 2023)
Objective We evaluated the usefulness of human epididymis protein 4 (HE4), a tumor marker, during and after treatment in patients with ovarian cancer (OC). Methods We included Japanese patients newly diagnosed with OC treated at the National Cancer Center Hospital between 2014 and 2021. The HE4 levels were measured in the serum stored during diagnosis. To evaluate the concordance between HE4 and the imaging results, we employed sequential pairs of blood sampling points and the results of imaging examinations. We compared the timing of the elevated HE4 levels, imaging diagnoses, and elevated cancer antigen 125 (CA125) levels in patients with recurrence. The Ethics Review Committee of our institution (2021-056) reviewed this study. Results Forty-eight patients with epithelial OC were eligible for enrollment. The sensitivity, specificity, and positive and negative predictive values of HE4 (criterion, 70 pmol/L) for disease progression during the follow-up period were 79.4%, 59.1%, 32.5%, and 92.0%, respectively (time point, n=317). We evaluated the relationship between HE4 and CA125 variability and disease status (recurrence or no recurrence). For recurrence, the sensitivity and negative predictive value of HE4 (criterion, 70 pmol/L), CA125 (criterion, 35 U/mL), and combination of HE4 and CA125 were 77.8%, 85.2%, and 92.6% and 75.0%, 82.6%, and 88.9%, respectively (n=48). Among the 27 patients who exhibited recurrence, 16 and nine showed earlier increased HE4 levels than the relevant imaging and CA125 levels, respectively. Conclusion HE4 may be a valuable marker for follow-up during and after OC therapy. A complementary role for HE4 and CA125 measurements was suggested for follow-up observations.